Wawasan Al-Qur’an tentang Mental Health, Studi Al-Qur’an Tematik dengan Pendekatan Grounded Theory - Annida Nazirah; Nadia Nurpadilah; Hanifatul Azizah; Muhammad Alif (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This research seeks to examine the teachings of the Qur'an thematic perspectives on mental health using a grounded theory approach. Even though the phrase "mental health" is not directly stated in the Qur'anic text, many verses convey concepts that align with modern psychological understanding, such as inner peace, emotional regulation, resilience during adversity, and spiritual healing. Through open, axial, and selective coding processes, six major subthemes emerged: inner peace and emotional balance, emotional resilience in facing life's challenges, spiritual therapy and healing, hope and spiritual optimism, self-acceptance, and spiritually guided life direction. The findings reveal that the Qur'an offers a holistic framework that is more than just theological as well as useful for maintaining mental and emotional stability. The verses analyzed reflect values that can serve as religious strategie for mental well-being, especially amid modern life complexities that often lead to stress, anxiety, and existential crises. This study highlights the significant contribution of Islamic spirituality-particularly Qur'anic wisdom-in promoting and strengthening mental health in both individual and communal contexts.